PROTECTION OF HEATING SURFACE DURING OUTAGE OF CALDRONS - Івасик, Ярослав Федорович; Якимів, Євген Миколайович; Кузнецова, Марта Ярославівна (Eastern-European Journal of Enterprise Technologies, 2012)
The defence methods of water-vapor and air-gas caldron highways are considered during an autage in reserve. The expenses of energy are appraised needed for protection of metal heating surfaces from outage corrosion.